Stress among diabetic mellitus patients with complication at Raja Perempuan Zainab II Hospital, Kota Bharu, Kelantan - M Jamsiah; I Zurainatul Irwani; WP Sh Ezat; SA Shamsul; MA Rahmah (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Studies on stress among diabetic patients with complications are not much conducted locally. In this study the researchers would like to find out the magnitude of the problem among the Malaysian. Methodology : A cross- sectional study was conducted to determine the prevalence of stress and its associated factors among the diabetes mellitus patients with complications at Raja Perempuan Zainab II Hospital, Kota Bharu, Kelantan. The translated Personal Stress Inventory questionairse was used to measure the stress among the respondents. Finding : The prevalence of stress was 36.8%. The study showed that the employment status of respondents has significant association with stress in which higher numbers of unemployed respondents were stressed as compared to the employed respondents. Other sociodemographic factors, namely duration of having diabetes mellitus and type of complications developed by the patients were not significant. Conclusion : Once the poor and unemployed patients were diagnosed to have diabetes mellitus either with or without complication, the health staffs should refer them immediately to the relevant agencies for help. By doing so, these patients could be prevented from having stress later. Outreach programmes in the community should be carried out regularly for an early detection and treatment of chronic diseases including diabetes mellitus to prevent patients from developing any complication.